Meta-analyses of the effects of high-intensity interval training in elite athletes—part I: mean effects on various performance measures - Wiesinger, Hans-Peter; Stöggl, Thomas Leonard; Haller, Nils; Blumkaitis, Julia; Strepp, Tilmann; Kilzer, Francesca; Schmuttermair, Anna; Hopkins, Will G. (Frontiers in Physiology, 2025)
IntroductionMeta-analysts have found that high-intensity interval training (HIIT) improves physical performance, but limited evidence exists regarding its effects on highly trained athletes, measures beyond maximum oxygen uptake (V˙O2max), and the moderating effects of different types of HIIT. In this study, we present meta-analyses of the effects of HIIT focusing on these deficits.MethodsThe effects of 6 types of HIIT and other moderators were derived from 34 studies involving highly trained endurance and elite athletes in percent units via log-transformation from separate meta-regression mixed models for sprint, time–trial, aerobic/anaerobic threshold, peak speed/power, repeated-sprint ability, V˙O2max, and exercise economy. The level of evidence for effect magnitudes was evaluated based on the effect uncertainty and the smallest important change of 1%.ResultsCompared with control training, HIIT showed good to excellent evidence for the substantial enhancement of most measures for some athlete subgroups in practically important study settings defined by effect moderators (maximum of 12.6%, for endurance female athletes after 6 weeks of aerobic traditional long intervals). The assessment of the moderators indicated good evidence of greater effects as follows: with more aerobic types of HIIT for V˙O2max (+2.6%); with HIIT added to conventional training for most measures (+1.1–2.3%); during the competition phase for V˙O2max (+4.3%); and with tests of longer duration for sprint (+5.5%) and time trial (+4.9%). The effects of sex and type of athlete were unclear moderators. The heterogeneity of HIIT effects within a given type of setting varied from small to moderate (standard deviations of 1.1%–2.3%) and reduced the evidence of benefit in some settings.ConclusionAlthough athletes in some settings can be confident of the beneficial effects of HIIT on some measures related to competition performance, further research is needed. There is uncertainty regarding the mean effects on exercise economy and the modifying effects of sex, duration of intervention, phase of training, and type of HIIT for most measures.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=236384.